2019
DOI: 10.4048/jbc.2019.22.e25
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Post-Mastectomy Radiotherapy in ypN0 Patients after Neoadjuvant Chemotherapy According to Molecular Subtypes

Abstract: Purpose The benefit of post-mastectomy radiation therapy (PMRT) in patients with breast cancer who achieve ypN0 following neoadjuvant chemotherapy (NAC) has not yet been established. This study aimed to identify the role of PMRT in patients who achieve ypN0 according to molecular subtype. Methods We identified patients initially suspected with axillary disease who achieved ypN0 following NAC. From 13 institutions of the Korean Radiation Oncology Group between 2005 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…A total of 189 patients were included in this analysis, and the effects of PMRT on locoregional control, DFS, and OS were evaluated. However, PMRT provides no additional survival benefits for any molecular subtype [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 189 patients were included in this analysis, and the effects of PMRT on locoregional control, DFS, and OS were evaluated. However, PMRT provides no additional survival benefits for any molecular subtype [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial search on PubMed yielded 1837 studies. After applying the inclusion and exclusion criteria, 13 studies were included in the meta-analysis [13] , [14] , [15] , [16] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis on the impact of LRRT on LRR included six studies ( Fig. 2 A) [15] , [20] , [21] , [22] , [23] , [24] . In total, 2388 patients with N+ at diagnosis and ypN0 after NACT were included in the analysis, 859 received LRRT and 1529 did not.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have determined a subpopulation of patients who benefited from PMRT, among those who received NAC. Scodan et al and Cho et al suggested that PMRT is beneficial in patients with ypN+ disease after receiving NAC, but not in those with ypN0 disease [ 21 , 29 ]. Furthermore, some researchers argued that PMRT can also be omitted in patients with ypN1 disease [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although no definite criteria have been established regarding the need for PMRT after NAC, several retrospective studies have performed this treatment [ 18 , 19 , 20 , 21 ]. As patients with a good response to chemotherapy have a better prognosis, the need for irradiation in these patients should be discussed, although existing guidelines recommend that the need for PMRT should be based on the pre-NAC staging [ 22 ].…”
Section: Introductionmentioning
confidence: 99%